2008
DOI: 10.1128/mcb.01152-07
|View full text |Cite
|
Sign up to set email alerts
|

RelA Ser276 Phosphorylation Is Required for Activation of a Subset of NF-κB-Dependent Genes by Recruiting Cyclin-Dependent Kinase 9/Cyclin T1 Complexes

Abstract: Infectious and inflammatory stimuli induce expression of gene networks controlling proinflammatory and innate immune responses. One important arm of the inflammatory response is mediated by monocyte-derived tumor necrosis factor (TNF), a cytokine that activates gene expression programs in adjacent epithelial cells to propagate mucosal inflammation (42, 51). Here, the spectrum of functional activities and the magnitude and timing of TNF-induced gene expression are important determinants of tissue homeostasis. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
173
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(184 citation statements)
references
References 62 publications
10
173
0
1
Order By: Relevance
“…Several studies have shown that reconstitution of p65-deficient mouse embryonic fibroblasts with p65 S205A, S276A, S281A, T435A, S468A, and S536A mutants leads to reduction of NF-B transcriptional activity confined to certain genes (12,20,(22)(23)(24)(25). Also, loss of glycogen synthase kinase-3␤ (GSK-3␤), which phosphorylates p65 at Ser-468 (26), has profound effects on the expression of interleukin-6 (IL-6) and chemokine (CC motif) ligand 2 (CCL2) genes, but it only minimally impacts IB␣ (NFKBIA) and chemokine (CXC motif) ligand 2 (CXCL2) expression (27).…”
mentioning
confidence: 99%
“…Several studies have shown that reconstitution of p65-deficient mouse embryonic fibroblasts with p65 S205A, S276A, S281A, T435A, S468A, and S536A mutants leads to reduction of NF-B transcriptional activity confined to certain genes (12,20,(22)(23)(24)(25). Also, loss of glycogen synthase kinase-3␤ (GSK-3␤), which phosphorylates p65 at Ser-468 (26), has profound effects on the expression of interleukin-6 (IL-6) and chemokine (CC motif) ligand 2 (CCL2) genes, but it only minimally impacts IB␣ (NFKBIA) and chemokine (CXC motif) ligand 2 (CXCL2) expression (27).…”
mentioning
confidence: 99%
“…CK2 forms a heterocomplex composed of two catalytic a subunits and two regulatory subunits (9). It was reported that CK2 phosphorylates p65 (10)(11)(12), an action critical for NF-kB-mediated transcription (13,14), although a detailed molecular mechanism of how CK2 regulates the transcription has not been shown.…”
Section: B Reakpoint Cluster Region (Bcr) Protein Is a Unique Kinasementioning
confidence: 99%
“…As one of the most abundant and well‐characterized NF‐κB dimer, P65 (RelA) translocate to nuclear and drive transcriptional response (Hayden & Ghosh, 2008; Karin & Ben‐Neriah, 2000; Vallabhapurapu & Karin, 2009). Phosphorylated form of P65/RelA is specifically required to activate transcriptional responses, including inflammatory response (Jamaluddin, Wang, Boldogh, Tian, & Brasier, 2007; Nicodeme et al., 2010; Nowak et al., 2008; Vermeulen, De Wilde, Van Damme, Vanden Berghe, & Haegeman, 2003; Zhong, SuYang, Erdjument‐Bromage, Tempst, & Ghosh, 1997). In this study, phosphorylated P65 was detected to be significantly up‐regulated following SAH induction.…”
Section: Discussionmentioning
confidence: 99%